أجناس العلل في "تهذيب سنن أبي داود لابن قيم الجوزية" -نماذج مختارة- - قرفي, عماره (جامعة الوادي university of eloued, 2023)
تعالج هذه المذكرة موضوع أجناس العلل الواردة في "تهذيب سنن أبي داود" لابن قيم الجوزية، والتي من خلالها نتعرف على مدى إسهامات هذا الإمام في ميدان العلل والنقد الحديثي عموما، فاخترنا نماذج معينة من الأحاديث تتبعنا وصنفنا أجناس العلل التي نستشفها من خلال معالجة المؤلف للحديث، كالتعليل بالتفرد أو الاضطراب وغيرها من الأجناس. This memorandum addresses the topic of the types of defects found in "Tahdhib Sunan Abi Dawood" by Ibn Qayyim al-Jawziyya. Through this, we can understand the contributions of this Imam in the field of hadith criticism (al-'Ilal) and examination, in general. We have selected specific examples of hadiths and classified the types of defects (al-'Ilal) that we deduce from the author's treatment of the hadith, such as the defect of singularity or confusion, and other types.
حديث
Keywords: أجناس العلل، التعليل بالتفرد، التعليل بالاضطراب، التعليل برفع الموقوف، التعليل بالاختصار، التعليل بالإدراج، تهذيب سنن أبي داود.; Types of Defects, Tahdhib Sunan Abi Dawood, defect of singularity or confusion